The COVID-19 Pandemic Impact on Away and Home Victories in Soccer and Rugby Union - Sedeaud, Adrien; De Larochelambert, Quentin; Schipman, Julien; Toussaint, Jean-Francois (Frontiers in Sports and Active Living, 2021)
Objective: To measure the impact of restrictions due to COVID on the proportion of matches won at home, away and draw in professional soccer and rugby union. Materials and Methods: Two samples of professional soccer and rugby union matches were collected from 2012-13 to 2020-21 seasons. For soccer, data involved first and second division matches of the England, Spain, Germany, Italy, France, Belgium, Scotland, Greece, Portugal and Turkey championships. For rugby union, championships concerned are Premiership Rugby, Celtic League, Top 14 and Pro D2. The proportions of home, away wins and draw were calculated and compared. A chi-square test of independence between years and types of result was realized to identify an overall inhomogeneity. Results: The proportion of away matches won between the 2012-13 and 2020-21 seasons increased significantly from 28.5 ± 1.2% to 32.5 ± 1.5% in soccer and from 38.0 ± 3.6% to 42.8 ± 5.0% in rugby union. In Premiership Rugby championship, the victory percentage at home dropped from 55.8 ± 3.1% when tifosi were present to 45.8 ± 12.8 % when they were not. Conclusion: The home advantage was drastically reduced in empty stadiums for several European soccer and rugby union professional championships. It vanished in the Premiership Rugby and Celtic League during the 2020-21 season.